Do River Otters Conform to Habitat Suitability Assessments?. (April 2016) - Holland, Angela; van der Merwe, Jorista
Abstract: River otters ( Lontra canadensis ) were reintroduced from 1994–1996 into parts of Illinois where the species was extirpated due to over harvest and habitat loss. At the time of reintroduction, managing for the persistence of the population through habitat was very important and research was conducted to determine which watersheds had quality habitat and which needed increased management and protection. In a study conducted in the mid‐1990s, biologists used pattern recognition (PATREC) modeling to identify high and low quality habitat for river otters at the subunit level (i.e., divided watershed), based on specific habitat attributes including wooded area, sinuosity, and wetland edge. We compared the habitat quality ratings of subunits with river otter use at 112 bridge sites from 2012–2014 to determine if river otters have distributed themselves according to previously determined habitat quality. We found that the PATREC model was a poor predictor of river otter use when sites were located close to the otter reintroduction points. The PATREC model was most likely a poor predictor of river otter use due to an over‐emphasis on the importance of woody vegetation to habitat suitability for river otter in the model. We recommend that future work on the assessment of habitat suitability for river otter use, and accuracy of this assessment, be conducted at a local spatial scale and over a shorter temporal scale. We also recommend that watershed policies and habitat assessments consider changes to land‐cover and follow an adaptive management approach to assess habitat suitability for reintroduced species.